ASSESMENT OF SOME HEAVY METALS IN WILD TYPE AND CULTIVATED PURSLANE (Portulaca oleracea L.) AND SOILS IN ISTANBUL, TURKEY - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2014)
Purslane (Portulaca oleracea L.) is an ornamental plant listed by the World Health Organization as one of the most used medicinal plants and a culinary herb for many countries. The present investigation was therefore conducted to evaluate heavy metal (cadmium, copper, lead and zinc) values in wild type and cultivated purslane, and soil samples collected in urban areas. Plant and soil samples were taken from two types of stations (brook coast and urban roadside) in two different districts (Bakirkoy and Zeytinburnu) of Istanbul. Standard procedures were used and the determinations of the elements in all samples were done using an Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES). It was observed that washing procedure reduced concentrations of all heavy metals. As a result of the measurements, the heavy metal values of washed and unwashed plant samples varied as; Cd (0.270.36 mu g/g dw), Cu (9.64-17.63 mu g/g dw), Pb (4.51-9.62 mu g/g dw) and Zn (32.69-59.49 mu g/g dw) for wild type and cultivated purslane samples. Heavy metal accumulations in plants reflected soil values in a proportional way especially for Cd, Cu and Zn. According to the results of this study, it can be said that both types of purslane reflect heavy metal amounts well in different areas with their washed and unwashed samples.
Keywords: Heavy metal; Istanbul; Plant; Portulaca oleracea L.; MUSCLE-RELAXANT PROPERTIES; STREET DUSTS; COMMON PURSLANE; TRACE-METALS; FATTY-ACIDS; VEGETABLES; EXTRACTS; CONTAMINATION; OMEGA-3-FATTY-ACIDS; CADMIUM